Fecal B-cell-activating factor as a new noninvasive marker in the evaluation of ulcerative colitis Egyptian patients: a comparative cross-sectional study - Hany A Hussein; Rasha S Mohamed (SpringerOpen, 2019)
Background and aim Diagnosis of ulcerative colitis (UC) is suspected clinically and confirmed through endoscopic biopsy. It can be followed-up and assessed by noninvasive biomarkers such as fecal calprotectin. Recently, B-cell-activating factor (BAFF) has been proposed to be a regulator of B-cell and T-cell immune responses and to be associated with inflammatory processes in autoimmunity. The aim of our study was to clarify the role of fecal BAFF as a simple predictor for disease activity and severity in patients with UC. Patients and methods Fifty Egyptian patients with UC were divided into two groups: group I including 40 patients with active UC (newly diagnosed) and group II including 10 patients with inactive UC (previously diagnosed); disease activity was assessed according to the Mayo activity scoring index; fecal BAFF and fecal calprotectin were measured for all patients using enzyme-linked immunosorbent assay. Results Significantly higher levels of Fecal BAFF and fecal calprotectin were found among patients with active UC, as compared with inactive UC patients. Fecal BAFF more than or equal to 50 μg/g had 97.5% sensitivity and 100% specificity in predicting disease activity in comparison with fecal calprotectin, which had a sensitivity and specificity of 90% at a cut off value more than or equal to 47 μg/g. In predicting disease severity, fecal BAFF more than or equal to 340 μg/g had a sensitivity of 95% and specificity of 100%, while fecal calprotectin more than or equal to 170 μg/g had a sensitivity of 80% and specificity of 95%. Conclusion Fecal BAFF is more sensitive and specific in predicting UC activity and severity than fecal calprotectin.